Aweb-Based Library Application Design At SMP Negeri 18 Medan - Titin Mega Andini Siahaan; Darmeli Nasution; Eko Hariyanto (Sean Institute, 2024)
The school library serves as a vital facility in educational institutions, providing a wide range of materials including books and non-books for teaching and learning purposes. SMP Negeri 18 Medan, located in North Sumatra, Indonesia, is equipped with its own school library. However, the management of these libraries is currently manual, with borrowing and returning recorded transactions using traditional methods, resulting in time-consuming processes for both recording and retrieving book data.